Nurses' voices - Nowak, Margaret; Bickley, Maureen (Curtin University of Technology, 2005)
In this paper the authors analyse aspects of the qualitative data from open-ended questionsincluded in the RN Survey 2002. The authors discuss the changes wrought by New PublicManagement (NPM) in the Australian and WA health sectors. They argue that therequisites of NPM and managerialism are not necessarily consistent with the historical roleof professionalism in the delivery of health care and of nursing as a health profession. Thenurses? qualitative responses are analysed using the framework from NPM andmanagerialism as a means to develop understanding of the issues and concerns expressedby nurses. The paper identifies three areas of dissonance: professional dissonance, careerchoice dissonance and ideological dissonance. It argues that, as a result, nurses emotionallyand professionally resist what has been termed ?the instrumental motivations ofmanagerialism?.